2017
DOI: 10.14202/vetworld.2017.630-635
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the growth performance of replacement female breeder goats through modification of feeding program

Abstract: Aim:The study was conducted at a smallholder goat farm located in Labu, Negeri Sembilan, Malaysia. The objective of this study was to evaluate the effect of proper feeding program on growth performances of replacement breeder goats.Materials and Methods:A total of 30 healthy female boer cross goats at the age of 4 months old with average initial live body weight (BW) of 20.05±0.5 kg were used for on-farm feeding trial to evaluate the growth performance as preparation for breeding purposes. The experimental goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
1
7
4
Order By: Relevance
“…Because fat did not improve bodyweight gain in the current study, this could explain the current finding for BCS in response to fat addition. Unlike the current results, Ghani et al (2017) reported increased BCS in growing female kids. In their study, the higher fat group had higher protein levels and the animals were younger.…”
Section: Resultscontrasting
confidence: 99%
“…Because fat did not improve bodyweight gain in the current study, this could explain the current finding for BCS in response to fat addition. Unlike the current results, Ghani et al (2017) reported increased BCS in growing female kids. In their study, the higher fat group had higher protein levels and the animals were younger.…”
Section: Resultscontrasting
confidence: 99%
“…Livestock voluntarily consume a certain amount of DM per day (measured in kg/day) to maintain health, growth, and production (Naik et al, 2014). The values of DM reported by Lounglawan et al (2014) as 18.93% in Napier grass harvested at 10 cm height on the 60 th day, Ghani et al (2017) as 13.04% in which Napier grass was harvested manually from pasture at the age of 8 weeks, Rahman et al (2014) as 20.79% were lower than the present finding, 26.01%. In the present investigation, the DM content in HMF was 24.75%, lower than Napier grass because of high moisture content.…”
Section: Chemical Composition Between Conventional Fodder and Hydropo...contrasting
confidence: 79%
“…The CP content of Napier grass investigated in the present study was 7.22%. The value was higher than the findings obtained by Zailan et al (2016) in common Napier grass harvested at an interval of 8 weeks as 6.44% and Ghani et al (2017) as 3.88%. The higher value of CP was reported by Rambau et al (2016) (Naik et al, 2013).…”
Section: Chemical Composition Between Conventional Fodder and Hydropo...contrasting
confidence: 69%
See 1 more Smart Citation
“…Buffaloes that were offered concentrate and bypass supplements had higher BCS due to better body weight gain. Similarly, buffaloes fed with concentrate have been shown to have good BCS [63], while cattle fed bypass fat showed improved feed intake [64]. On the other hand, the addition of 4 kg/d to 8 kg/d of concentrates for five weeks was able to improve the body mass gain without changes in BCS of dairy cows [65], while another study revealed that additional bypass fat did not improve body weight gain and BCS [66].…”
Section: Discussionmentioning
confidence: 99%